BEN JONSON’S “THE ALCHEMIST” CHARACTERS - Fayzullayeva Munisa Fozil qizi; Baisov Ahmad Sobirjonovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT This article provides a concise analysis of the characters in Ben Jonson’s play “The Alchemist.” Set in Jacobean London, the play satirizes alchemy and human folly through characters like the cunning Subtle, the credulous Lovewit, and the ambitious Dapper, Drugger, and Face. Through examining their personalities and interactions, the study reveals themes of deception and greed. Jonson’s use of distinct character types  and  comedic  techniques  entertains  while  critiquing  societal  corruption.  This analysis offers insights into Jonson’s craftsmanship and enduring social commentary in early modern drama. Ben Jonson’s “The Alchemist” is a classic Jacobean drama that uses satire to condemn  the  moral  deterioration  and  societal  avarice  of  its  period.  This  abstract examines how Jonson satirises the church, law, and nobility throughout the play, as well as greed and its corrupting effects. This abstract shows Jonson’s brilliant reflection on human nature and the hazards of uncontrolled ambition through characters, story, and language. The ancient cautionary tale “The Alchemist” encourages audiences to consider the dangers of wealth and moral compromise.